Bacteriostatic repair-promoting hydrogel dressing and preparation method thereof
By constructing micro-nano-scale topological structures on the surface of the implant, forming hydroxyapatite coatings and chemical grafting technology to fix bioactive molecules, the shortcomings of implant materials in bone integration performance are solved, and local bone regeneration and stability improvement around the implant is achieved.
Patent Information
- Application Number
- CN202510307710.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-17
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-03-17
AI Technical Summary
The existing implant materials have shortcomings in bone integration performance, especially when the mandible bone volume of yellow people is small, the stability and lifespan of the implant cannot meet clinical needs.
The bone conductivity of the implant is enhanced by constructing a micro-nano-scale topology on the surface of the implant and forming a hydroxyapatite coating using plasma spraying technology. At the same time, chemical grafting technology immobilizes bioactive molecules on the titanium-based surface and introduces RGD polypeptide sequences to regulate cell adhesion behavior.
These technical means effectively improve the bone integration performance of the implant, promote local bone regeneration around the implant, and improve the stability and lifespan of the implant.
Smart Images

Figure CN119792485A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of dental dressings, and in particular relates to an antibacterial and repair-promoting hydrogel dressing and a preparation method thereof. Background Art
[0002] The loss of teeth / dentition is the most important type of disease in oral clinical work. The loss of natural teeth deteriorates the normal chewing function of the oral and maxillofacial system, and changes the facial appearance, affecting the aesthetics. The instability and loss of occlusal relationship will cause disorder or even lesions in the temporomandibular joint, seriously affecting the patient's quality of life and affecting physiological and psychological functions. Implant denture restoration can greatly improve the chewing efficiency after restoration treatment without damaging adjacent teeth. It has the characteristics of high comfort and long durability that conventional restoration methods do not have, and is increasingly becoming the preferred choice in the process of tooth loss restoration treatment.
[0003] The origin of modern oral implant restoration technology can be traced back to the mid-1950s and 1960s, when Professor Branemark from Sweden and his colleagues first proposed the phenomenon of bone integration and pure titanium implants, that is, after the pure titanium implant is implanted in the body and heals, a tightly integrated interface is formed between the pure titanium implant and the surrounding bone tissue, with a direct structural and functional connection. This physiological phenomenon is also the basis for the implant to remain stable in the bone tissue and perform its functions. After a long period of development, the types of oral implants have become diversified. According to different implantation times and methods, they can be divided into one-stage and two-stage implants; according to the implantation site, they can be divided into intraosseous and zygomatic implants; and according to the different general shapes of the implant, they can be divided into columnar, conical, and root-shaped implants.
[0004] As an implantable medical device, implant materials should have high biocompatibility and exhibit specific physiological functions on the basis of good biosafety. In addition, in view of the special physical and chemical environment in the oral cavity, they must also have excellent mechanical and corrosion resistance to meet practical applications. In particular, in view of the clinical situation that the mandibular bone mass of Asians is smaller and the implant space is less than that of Europeans and Americans, and a large number of narrow-diameter implants are needed, new implant materials should meet the characteristics of "high (mechanical) strength, low (elastic) modulus, and narrow diameter". Such clinical needs have also put forward new requirements and directions for the development and research of implant materials.
[0005] Pure titanium material, as the cornerstone of the development of implants, is the mainstream material of the current implant system. With the great progress in materials science and processing technology, the development and utilization of various materials with good performance to further improve the comprehensive performance of implants and expand the application scope and applicable scenarios of implants have important research significance and practical value. At present, new implant materials are emerging in an endless stream, mainly including metal materials represented by pure titanium and its alloys, ceramic materials, and organic polymer materials. These materials have different biological and mechanical properties.
[0006] Titanium and titanium alloys, as bioinert materials, face the challenge of insufficient osteoinduction in clinical applications, and their osteointegration performance needs to be improved through multi-dimensional technologies. Constructing micro-nanoscale topological structures on the surface of implants can simulate the three-dimensional pore characteristics of natural bone tissue and promote the directional migration and mineralization deposition of osteoblasts. Related technologies have been verified in the high-precision component processing in the aviation field. The formation of hydroxyapatite coatings through plasma spraying technology not only enhances the osteoconductivity of implants, but also activates osteogenic signaling pathways through calcium-phosphorus ion gradient release. The principle of this technology is similar to the preparation process of thermal protection coatings for spacecraft.
[0007] Chemical grafting technology can fix bioactive molecules on titanium-based surfaces. For example, the introduction of arginine-glycine-aspartic acid (RGD) polypeptide sequences can regulate cell adhesion behavior by specifically recognizing integrin receptors. This type of molecular modification strategy has been successfully applied in the processing of flexible sensor substrates.
[0008] The temperature-sensitive hydrogel system utilizes the phase change properties of temperature-sensitive materials such as poly (N-isopropylacrylamide) to achieve gelation encapsulation at physiological temperature and precisely control the sustained-release kinetics of bone growth promoters such as bone morphogenetic protein (BMP). This controlled-release mechanism has technical commonalities with the intelligent response characteristics of high-end engineering plastics.
[0009] Temperature-sensitive hydrogel systems can bring many clinical advantages and provide a suitable environment for local bone regeneration around implants. Due to the high water content of the temperature-sensitive hydrogel system, bone growth promoters such as BMP-2 can be easily loaded in a solution state by a simple mixing method. Due to the temperature-dependent gelation properties of the system, it can be easily applied to the human body at room temperature. In addition, it does not require surgical procedures or additional external factors to form hydrogels. This temperature-sensitive property and injectable properties are very convenient for patients. In addition, the hydrophilic environment and high porosity of the hydrogel system are conducive to cell infiltration, vascularization, and subsequent bone regeneration.
[0010] The special physiological structure and environment of the oral cavity lead to difficulties in oral administration. Therefore, there is an urgent need for a drug carrier to solve the problem of oral administration. Polyoxyethylene-polyoxypropylene copolymer (Poloxamer 407) or carbomer can form a thermosensitive biogel with good mechanical properties and mucoadhesion properties. This biogel can be designed as a drug supply platform for oral implantable drug delivery systems. Local administration is usually used to treat local diseases such as periodontitis, oral rash and other oral diseases. The main advantage of this drug delivery method is that it can deliver bioactive agents directly to the diseased area, maintain the required drug concentration for a considerable period of time, and ensure good retention at the site of administration. Below the sol-gel transition temperature, the fluidity and compression properties of the preparation are extremely low. In contrast, under conditions above the sol-gel transition temperature, these preparations exhibit a wide range of viscoelasticity, mechanical properties and mucoadhesion properties, which will help them be used in specific parts of the oral cavity. High elasticity and mucoadhesion will make preparations containing poloxamer 407 an effective platform for controlling local drug delivery in the oral cavity. Currently, thermosensitive gel dressings have been widely used to treat various periodontal diseases, and there are many types of preparations, such as studies on the treatment of periodontitis with moxifloxacin hydrochloride in situ gel, injectable in situ curcumin gel for the treatment of periodontal pockets, thermosensitive gel for the treatment of oral herpes infections, and clinical cases of thermosensitive gel as a stent encapsulation system.
[0011] Professor Xu Wenfang of Shandong University conducted research on L-isoserine tripeptide derivatives as aminopeptidase inhibitors and obtained a series of L-isoserine tripeptide derivatives. The relevant research results were published in the Journal of Enzyme Inhibition and Medicinal Chemistry. The title of the article is Design, synthesis and biological evaluation of novel L-isoserine tripeptide derivatives as aminopeptidase N inhibitors, which is translated into Chinese as: Design, synthesis and biological activity evaluation of novel L-isoserine tripeptide derivatives as aminopeptidase N inhibitors.
[0012] The article focuses on the research of novel L-isoserine tripeptide derivatives as aminopeptidase N (APN) inhibitors, covering design, synthesis, biological activity evaluation and other aspects, aiming to develop new anticancer drugs. The study takes compound 14b as the lead to design and synthesize novel L-isoserine tripeptide derivatives. Except for compound 16j, other target compounds have inhibitory activity. In terms of in vitro APN inhibitory activity, compound 16l has the strongest inhibitory activity , slightly better than The tyrosine group may enhance the interaction with APN through hydrogen bonding, and the phenyl group at the R1 position is more conducive to improving the activity than the benzyl group. The inhibitory activity of series 2 compounds is similar to that of series 1 compounds, but the water solubility is significantly reduced. The results of the cell level experiment are basically consistent with the enzyme level experiment, but the inhibitory activity of compound 16l on A549 cells is weak, which may be related to the differences in the binding characteristics of APN in different species.
[0013] In terms of antiproliferative activity, some compounds showed similar or even better antiproliferative effects than Bestatin on different tumor cell lines, but compound 16l did not show outstanding activity in the antiproliferative experiment. Moreover, the compounds that performed well in the APN inhibition experiment did not show more outstanding antiproliferative activity on cells with high APN expression than those with low APN expression, suggesting that the antiproliferative mechanism of these compounds may be different from the mechanism of inhibiting APN. Molecular docking revealed that compound 16l had a similar binding mode to Bestatin, with its L-isoserine moiety coordinating with the zinc ion of APN, the phenyl moieties of phenylalanine and tyrosine residues inserted into the S1 pocket of APN, and the leucine moiety inserted into the S1′ pocket, and formed hydrogen bonds with multiple amino acid residues, enhancing the binding affinity, while the chloramphenicolamine residue of compound 16j did not enter the S1′ pocket, resulting in activity differences.
[0014] 16j synthesized in the article has the chemical formula , molecular weight 426.18, chemical name 2-(3-amino-2-hydroxypropionamido)-3-hydroxy-3-(4-nitrophenyl) propionylleucine, chemical structure is as follows: .
[0015] However, there is no report on other activities or uses of the above-mentioned 16j structure (hereinafter referred to as compound A) in existing literature and patents. Summary of the invention
[0016] As a dentist, the inventor has conducted in-depth research on dressings that promote local bone regeneration around implants. The study found that compound A can be used as the main component of the dressing to prepare a temperature-sensitive hydrogel dressing to promote local bone regeneration around implants, thereby promoting the repair of alveolar bone wounds after implantation. It was unexpectedly found that compound A has a significant antibacterial effect on common oral bacteria.
[0017] The present application discloses for the first time the use of compound A for preparing a dressing for promoting local bone regeneration around an implant.
[0018] The chemical structure of compound A is as follows: .
[0019] The implant material is one of titanium, titanium alloy and ceramic.
[0020] The implant material is one of surface-modified titanium, titanium alloy and ceramic.
[0021] The present application further discloses the use of compound A for preparing a dressing for inhibiting bacterial growth around implants.
[0022] The dressing is a hydrogel dressing.
[0023] The mass percentage concentration of compound A in the dressing is 0.1%-5%.
[0024] The mass percentage concentration of compound A in the dressing is 1.5%.
[0025] The mass percentage concentration of compound A in the dressing is 2%.
[0026] The dressing is a temperature-sensitive hydrogel dressing.
[0027] The temperature-sensitive hydrogel dressing is injected around the implant through a syringe, and plays the role of inhibiting bacteria and promoting the growth of alveolar bone, promoting the fusion of the wound between the alveolar bone and the implant, and extending the life of the implant.
[0028] The temperature-sensitive hydrogel dressing uses poloxamer 407 as a hydrogel matrix.
[0029] The preparation method of the temperature-sensitive hydrogel dressing is as follows: 1) Dissolve compound A in phosphate buffer; 2) Poloxamer 407 is added to the solution obtained in step 1) while stirring, and after the poloxamer 407 is completely dissolved, the solution is added to a phosphate buffer solution to make up the volume; 3) Take the gel solution obtained in step 2), dispense it into vials, add rubber stoppers, and roll aluminum caps to obtain the product.
[0030] Beneficial effects of the present invention: The present application first discovered that compound A has significant antibacterial activity against common oral bacteria, and after being prepared into a temperature-sensitive hydrogel dressing, it still has antibacterial activity. Injecting it around the implant can prevent alveolar bone reduction, stimulate vertical bone regeneration around the implant, increase bone mass to improve the stability of the implant, and ultimately promote the fusion of the wound between the alveolar bone and the implant, extending the life of the implant.
[0031] Abbreviations: TSB medium: Trypticase Soy Broth (TSB); BHI medium: Brain Heart Infusion Medium (Brain Heart Infusion Medium); RPMI1640 medium: RPMI 1640 medium prepared by Roswell Park Memorial Institute (Roswell Park Memorial Institute, USA); MH medium: Mueller-Hinton medium. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Attached Figure 1 : Effects of Example 3-5 Hydrogel Dressing and Comparative Example Dressing on Promoting Alveolar Bone Formation Around Titanium Implants (n=4) Attached Figure 2 :Effects of Example 3-5 Hydrogel Dressing and Comparative Example on Vertical Bone Growth Height around Titanium Implants (n=4) DETAILED DESCRIPTION
[0033] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0034] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0035] Example 1 Preparation of Compound A Hydrogel Dressing 1) Dissolve 0.1 g of compound A in 70 ml of phosphate buffer (pH 7.4, 100 mM).
[0036] 2) 15.0 g of poloxamer 407 was added to the solution obtained in step 1) while stirring. After the poloxamer 407 was completely dissolved, it was added to phosphate buffer (pH 7.4, 100 mM) and the volume was adjusted to 100 ml; 3) Take the gel solution obtained in step 2 and dispense it into vials, 0.5 ml per bottle, add rubber stoppers, and roll aluminum caps to obtain the product.
[0037] Comparative Example: According to the preparation process of Example 1, without adding compound A, a 15% poloxamer 407 hydrogel dressing was prepared as a comparative example.
[0038] Example 2-6 Preparation of hydrogels with different concentrations of compound A According to the preparation process of Example 1, only the amount of compound A added in step 1) was changed to prepare hydrogel dressings containing 0.5%, 1.0%, 1.5%, 2.0%, and 5.0% respectively, which were defined as hydrogel dressings of Examples 2-6 respectively.
[0039] Example 7 Antibacterial experiment of compound A (implemented with reference to Chinese patent CN113679632B) 7.1 Experimental Methods (1) Strain culture Candida albicans ATCC SC5314 was cultured in RPMI 1640 medium at 37°C and 80% humidity. Incubate under the conditions of Staphylococcus aureus ATCC 6538 in TSB medium, 37°C, Incubate under the conditions of Methicillin-resistant Staphylococcus aureus 18908 (MRSA 18908) in TSB medium, 37°C, Incubate under the conditions of Porphyromonas gingivalis ATCC 33277 was cultured in BHI medium with hemin (haemin, 5 μg / mL) and menadione (1 μg / mL) added at 37°C under strict anaerobic conditions. Streptococcus mutans Clarke ATCC UA159 was cultured on brain heart infusion agar at 37°C. Cultivated under conditions; Streptococcus sanguis ATCC 10556, brain heart infusion agar medium, 37℃, Cultivated under conditions.
[0040] (2) Sample Dissolve compound A in distilled water to a concentration of 10 mg / mL, prepare a total of 20 ml, and store in a refrigerator at 4°C until use.
[0041] (3) Determination of minimum inhibitory concentration (MIC) With reference to the Clinical and Laboratory Standards Institute (CLSI) regulations, the microbroth two-fold dilution method was implemented to determine the minimum inhibitory concentration (MIC) of compound A against different microorganisms. This method is recognized as an effective method by the Clinical and Laboratory Standards Institute (CLSI), with a wide and common application range. It can quickly detect the effects of drug interactions in a short period of time, and can draw reliable conclusions through further analysis of experimental data. The results are stable and highly reproducible.
[0042] For Candida albicans ATCCSC5314, the test strain was adjusted to a concentration of After that, the bacterial suspension was diluted to Prepare the test bacterial solution. Take 200μL of the test bacterial solution and add it to the first well of a flat-bottomed 96-well plate, and then add 100μL of the test bacterial solution to each well. Add 2μL of the test compound stock solution to the first well (the concentration of compound A in the well is 100μg / mL), pipet and mix in the first well, take 100μL of the uniform suspension, add it to the second well, pipet and mix, repeat to the last well, and discard the excess bacterial solution. Incubate the 96-well plate at 37°C for 24 hours. MIC is defined as the minimum drug concentration that can inhibit the growth of microorganisms by naked eye observation. The experiment was repeated in three groups, and econazole was selected as the positive control.
[0043] For Staphylococcus aureus ATCC 6538 and methicillin-resistant Staphylococcus aureus 18908, MH medium was used to adjust the test strains to a concentration of , prepare the test bacterial solution. Take 200μL of the test bacterial solution and add it to the first well of a flat-bottomed 96-well plate, and then add 100μL of the test bacterial solution to each well. Add 2μL of the test compound stock solution to the first well (the concentration of compound A in the well is 100μg / mL), pipette and mix in the first well, take 100μL of the uniform suspension, add it to the second well, pipette and mix, repeat to the last well, and discard the excess bacterial solution. Place the 96-well plate at 37°C, The experiment was repeated for 24 hours under the same conditions, and vancomycin was used as a positive control.
[0044] For Streptococcus mutans ATCC UA159 and Streptococcus sanguis ATCC 10556, the test strains were adjusted to a concentration of , prepare the test bacterial solution. Take 200μL of the test bacterial solution and add it to the first well of a flat-bottomed 96-well plate, and then add 100μL of the test bacterial solution to each well. Add 2μL of the test compound stock solution to the first well (the concentration of compound A in the well is 100μg / mL), pipette and mix in the first well, take 100μL of the uniform suspension, add it to the second well, pipette and mix, repeat to the last well, and discard the excess bacterial solution. Place the 96-well plate at 37°C, The experiment was repeated for three times, and vancomycin was selected as a positive control.
[0045] For Porphyromonas gingivalis ATCC33277, hemin (5 μg / mL) and vitamin K (1 μg / mL) were added to BHI medium and the test strain was adjusted to a concentration of , prepared as the test bacterial solution. Take 200μL of the test bacterial solution and add it to the first well of a flat-bottomed 96-well plate, and then add 100μL of the test bacterial solution to each well. Add 2μL of the test compound stock solution to the first well (the concentration of compound A in the well is 100μg / mL), mix it by pipetting in the first well, take 100μL of the uniform suspension, add it to the second well, mix it by pipetting, repeat to the last well, and discard the excess bacterial solution. Incubate the 96-well plate at 37°C under strict anaerobic conditions for 24 hours. MIC is defined as the minimum drug concentration that can inhibit microbial growth by naked eye observation. The experiment was repeated in three groups, and chlorhexidine was selected as the positive control.
[0046] 7.2. Antibacterial test results Table 1 Minimum inhibitory concentration MIC value of compound A .
[0047] Table 1 shows the antibacterial results of compound A against common oral bacteria. From the results in the table, it can be seen that compound A has significant antibacterial effects on Candida albicans, Staphylococcus aureus, MRSA, Streptococcus mutans, Streptococcus sanguis and Porphyromonas gingivalis, and the MIC values are between 12.5-50 μg / mL.
[0048] Example 8 Gelation of the temperature-sensitive hydrogel dressings of Examples 1-6 and Comparative Examples When the temperature changes, the aqueous solution of poloxamer 407 hydrogel undergoes a thermosensitive phase change. The solution remains in a solution state at room temperature. When the temperature rises, gelation occurs and the viscosity of the gel increases sharply. When the temperature rises to 37°C, the viscosity of the hydrogel dressings obtained in the comparative example and Examples 1-6 changes greatly. The tilt method confirms that a gel state is formed under body temperature conditions.
[0049] In addition, the loaded drug can change the hydrophobic / hydrophilic ratio, so the gelation characteristics will be affected by the loaded drug. Therefore, loading compound A will affect the temperature-sensitive properties of poloxamer 407 hydrogel. In order to confirm the gelation properties of poloxamer 407 hydrogel loaded with compound A at body temperature, the gelation temperatures of the hydrogel dressings obtained in Examples 1-6 and the comparative example were studied. The results showed that the gelation temperatures of the hydrogel dressings obtained in Examples 1-6 did not change significantly compared with the poloxamer 407 hydrogel (comparative example) not loaded with compound A.
[0050] The hydrogel dressings obtained in Examples 1-6 and the comparative example were gradually heated up (heating rate of 0.5°C / min) under continuous stirring (rotation speed of 100 rpm). The temperature was set by a constant temperature water bath, and the temperature inside the sample was controlled by a precise thermometer (accuracy of ±0.1°C). When the stirring bar (length 25 mm, diameter 6 mm) stopped moving due to gelation, the temperature displayed at this time was recorded as the temperature at which the solution turned into gel, i.e., the gelation temperature.
[0051] Table 2 Gelation temperature of the hydrogel dressings obtained in Examples 1-6 and the hydrogel dressings of the comparative example .
[0052] Example 9 Study on bone formation in situ after single injection of the hydrogel dressings obtained in Examples 1-6 and Comparative Examples Male C57BL / 6 mice aged 6 weeks and weighing 18-20 grams were randomly divided into eight different groups, with 5 mice in each group. The hydrogel dressings obtained in Examples 1-6 and the comparative example and saline were administered respectively. After shaving each mouse, 200 μL of hydrogel dressings of different formulations or saline was injected subcutaneously on the back. After 8 weeks, the mice were killed by carbon dioxide asphyxiation, and then specimens of each group were collected at and around the injection site. The specimens were carefully removed, fixed in 10% neutral buffered formalin solution for 24 hours, and then transferred to 70% ethanol.
[0053] The bone formation ability of the hydrogel dressings obtained in Examples 1-6 and the comparative example was evaluated in situ by a single injection.
[0054] Eight weeks after injection, bone formation was assessed by soft X-ray and micro-computed tomography (μ-CT). Irregular spherical bone formation was observed at the injection site.
[0055] According to the formula, the increased bone tissue volume = the bone tissue volume observed in the dressing group - the bone tissue volume observed in the control group, in cubic millimeters. The experimental data are as follows: Table 3 Increased bone tissue volume of experimental mice in each group
[0056] .
[0057] As the concentration of compound A in the hydrogel dressing increased, the bone tissue formed gradually became larger, but after the concentration increased to 2%, that is, when the concentration increased to 5%, the bone tissue formed did not increase significantly compared with the hydrogel dressing with a concentration of 2%. No bone-like tissue was observed in the control group.
[0058] Eight weeks after injection, all the formed hydrogels disappeared completely. No inflammatory response was observed in any experimental group. These non-toxic reactions indicate that the hydrogel dressings obtained in Examples 1-6 have excellent biocompatibility. The surrounding cells can infiltrate the hydrogel dressings well, and the compound A continuously released from the hydrogel dressings contributes to cell survival, differentiation and bone tissue formation.
[0059] Example 10 Titanium implant implantation experiment in beagle dogs 10.1 Implantation of titanium implants: All surgeries were performed under aseptic conditions under general and local anesthesia using a mixture of cimetidine hydrochloride, cefazolin sodium, dexmedetomidine, and tiletamine / zolazepam. Anesthesia was maintained using isoflurane and 100% oxygen.
[0060] After extracting the mandibular teeth from the first premolar to the first molar of two beagles, the incision sites were sutured with 4-0 nylon thread. After 8 weeks, four bone defects with a height of 3 mm and a length of 16 mm were made on the left and right mandibules using a water-cooled rotary dental drill. A total of 16 titanium implants were implanted, 2 implants in each bone defect, and 8 implants in each dog. The distance between the implants was about 4 mm, and the upper 4 mm of the implant was exposed outside the alveolar bone. The control group (four implants) used 250 μL of the hydrogel dressing prepared in the comparative example at the bone defect, and after gelation, the wound was immediately sutured with 4-0 nylon thread. The experimental group used 250 μL of the compound A hydrogel dressing prepared in Examples 3-5 at the bone defects where the remaining twelve implants were located, and each example group had four implants. After the polymer solution was gelled by body temperature, the wound was immediately sutured with 4-0 nylon thread.
[0061] Amoxicillin and meloxicam were taken orally for 7 consecutive days after surgery, the former twice a day and the latter once a day. During the experiment, 2% chlorhexidine gluconate was used to rinse the mouth every day to maintain oral hygiene.
[0062] 10.2 Clinical Observation The surgical procedure was uneventful for the animals. The health status of the animals was checked daily, the dogs were active, and the healing process was proceeding naturally. Tooth extraction, alveolar ridge modification, and titanium implant placement were completed according to the study protocol.
[0063] The experimental design is summarized in Table 4. A defect with a height of 3 mm and an area of 4×16 mm was created on the mandible of a beagle dog using a water-cooled rotary dental drill. After the titanium implant was placed, the freshly prepared Example 3-5 hydrogel dressing was spread on it to completely cover the bone defect and the titanium implant. After a few seconds, the formation of a solid gel was confirmed. Subsequently, the exposed tissue was sutured. Within 12 weeks after treatment, all jaw quadrants were completely healed without wound healing failure or inflammatory response.
[0064] Table 4 Experimental design of titanium implants in beagle dogs .
[0065] 10.3 Imaging observation: Two-dimensional images of the mandible were monitored using a portable X-ray machine at 4 and 12 weeks after surgery. For three-dimensional analysis, each specimen was scanned by micro-CT in cone-beam acquisition mode. The volume and mineral density of the newly formed bone were measured using a CT analysis program. Three-dimensional surface rendering images were produced using Mimics version 14.0 imaging software.
[0066] After tooth loss, alveolar ridge bone resorption and alveolar bone height reduction are expected to occur, which may reduce the stability of the implant, reduce the life of the implant, and cause trouble for the patient to have a second implant. In some cases, the compound A hydrogel dressing prepared in this application is expected to prevent alveolar bone reduction, stimulate vertical bone regeneration around the implant, increase bone mass, and improve the stability of the implant.
[0067] After treating the critical defect area around the implant with the hydrogel dressing of Example 3-5, the changes of the alveolar bone defect over time were monitored by intraoral X-ray. In the control group, slight bone resorption and implant exposure occurred around the implant over time. Compared with the control group, obvious bone regeneration was observed in the hydrogel dressing group loaded with compound A prepared in Example 3-5, and the exposed threads of the implant were completely covered by new bone, and the degree of coverage of the threads by new bone increased with the increase of the content of compound A in the dressing.
[0068] 10.4 Histological observation: After 12 weeks of treatment, the effects of the hydrogel dressings of Examples 3-5 on bone regeneration were evaluated by X-ray and micro-computed tomography (CT).
[0069] For histological analysis, the mandible including the implants was removed using a high-speed water-cooled diamond saw and the EXAKT cutting system.
[0070] The degree of bone regeneration was studied by X-ray and micro-CT scanning. There were significant differences in the height of the bone tissue around the implants in the four groups. In fact, the exposed area of the control group was rarely covered by regenerated bone. However, after treatment with the hydrogel dressing of Example 3-5, a significant amount of bone regeneration was shown around the implant wall, and it increased with the increase in the content of compound A in the dressing. Most areas of the implant threads in the hydrogel dressing group of Example 3-5 were wrapped by vertically growing bone tissue. Compared with the control group, the bone volume of the hydrogel dressing group of Example 3-5 increased significantly. The bone volume of the hydrogel dressing of Example 3-5 in the area of interest (the bone volume was measured from the innermost point of the implant thread to 0.5 mm from the starting point) was 34.86 mm³, 35.74 mm³ and 35.81 mm³, respectively, and the bone tissue completely covered the thread. The bone volume of the control group was only 23.73 mm³, and the implant thread could still be observed. In summary, compared with the control group, the bone regeneration effect of the hydrogel dressing of Example 3-5 was increased by 1.47 times, 1.50 times and 1.55 times, respectively. In addition, there is also a difference in bone mineral density (measured from the innermost point of the implant thread to 0.5 mm from the starting point) between the hydrogel dressings of Examples 3-5 and the control group. Specific experimental data are as follows: Table 5 Effect of Examples 3-5 and Comparative Example Hydrogel Dressings on Promoting Alveolar Bone Formation Around Titanium Implants
[0071] .
[0072] 10.5 Histomorphometric analysis: All specimens were dehydrated through a series of graded alcohol concentrations. After dehydration, the specimens were embedded in acrylic resin. Longitudinal sections containing tissues and implants were obtained using a high-speed water-cooled diamond saw and the EXAKT cutting system.
[0073] Histomorphometric analysis was performed using an optical microscope and the Image-Pro Plus image analysis system. The central section of each implant was used for histomorphometric analysis. The induced bone height (mm) was measured at 0.5 mm, 1.0 mm, and 2.0 mm from the implant.
[0074] Histomorphometric analysis was performed to assess the extent of regenerated bone. Quantitative assessment showed that there were significant differences in vertical bone growth in the bone tissue surrounding the implants of the four test groups. Vertical bone increments were measured at each point 0.5 mm, 1.0 mm, and 2.0 mm from the implant wall. The control group had limited bone regeneration along the implant wall from the defect interface. However, the bone height of the hydrogel dressing group of Example 3-5 was significantly higher than that of the control group at all measurement points.
[0075] The vertical bone growth height measured in the hydrogel dressing group of Example 3-5 was 0.33-0.44 mm from the implant wall surface to 2.0 mm from the implant. The bone height of the hydrogel dressing group of Example 3-5 at each point was much higher than that of the control group. The specific experimental data are shown in Table 6.
[0076] Table 6 Effects of Examples 3-5 and Comparative Example Hydrogel Dressings on Vertical Bone Growth Height around Titanium Implants
[0077] .
[0078] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. Use of compound A for preparing a dressing for promoting local bone tissue regeneration around an implant, characterized in that: The chemical structure of compound A is as follows: 。 2. The use according to claim 1, characterized in that The implant material is one of titanium, titanium alloy and ceramic.
3. The use according to claim 1, characterized in that The implant material is one of surface-modified titanium, titanium alloy and ceramic.
4. The use according to claim 1, characterized in that The compound A is used for preparing a dressing for inhibiting bacterial growth around implants.
5. The use according to claim 1, characterized in that The dressing is a hydrogel dressing.
6. The use according to claim 1, characterized in that The mass percentage concentration of compound A in the dressing is 0.1%-5%.
7. The use according to claim 6, characterized in that The mass percentage concentration of compound A in the dressing is 1.5%.
8. The use according to claim 6, characterized in that The mass percentage concentration of compound A in the dressing is 2%.
9. The use according to any one of claims 5 to 8, characterized in that: The dressing is a temperature-sensitive hydrogel dressing.
10. The use according to claim 9, characterized in that The preparation method of the dressing is as follows: 1) Dissolve compound A in phosphate buffer; 2) Poloxamer 407 is added to the solution obtained in step 1) while stirring, and after the poloxamer 407 is completely dissolved, the solution is added to a phosphate buffer solution to make up the total volume; 3) Take the gel solution obtained in step 2), dispense it into vials, add rubber stoppers, and roll aluminum caps to obtain the product.
Citation Information
Patent Citations
Application of antimicrobial peptide compound DM80Bu20 in the preparation of antibacterial toothpaste
CN113679632B
5-position modified pyrimidines and their use
CN102985435A
Anti-microbial healing-promoting hydrogel dressing and preparation method therefor
CN103520767A
Multifunctional hydrogel capable of resisting inflammation and promoting bone repair as well as preparation method and application of multifunctional hydrogel
CN116327895A
Oral wound dressing and preparation method thereof
CN118949003A
Cited By
Bacterial biofilm inhibiting and disinfecting composition and disinfecting method
CN120501122A